Lines - Yenawine, Philip (New York : Museum of Modern Art : Delacorte Press, 1991)
Isolates the artistic element of lines, discusses what thoughts and feelings can be conveyed by different kinds of lines, and examines how they contribute to a work of art through various examples.
*SLJ*
1.9
K-3
Keywords: Line (Art) -- Juvenile literature; Line (Art); Art appreciation; Line (Art); Art appreciation